Konflik Laut Cina Selatan di Wilayah Natuna dalam Menempuh Penyelesaian Sengketa Menurut Perspektif Hukum Internasional - Nafis, Muhammad; Akbar, Rizki (Lembaga Yasin AlSys, 2025)
The problem of territorial status and unclear state boundaries often arises from the core of a conflict or dispute between adjacent countries, one of which is the dispute that occurs is the South Cina Sea in the Natuna region as the dispute in the South Cina Sea occurs because of the unilateral claim of the Chinese government to issue a unilateral map in the South Cina Sea. The background of this writing is the existence of a form of dispute resolution and influence for Indonesia in the South Cina Sea dispute. The type of research in this writing is research based on normative law. Meanwhile, the types of approaches in this study are the legislative approach, and the case approach. The results of the study show that the influence for Indonesia in the dispute over the South Cina Sea area in Natuna can be seen from several interests carried out by Indonesia in the disputed area, including sovereignty, economic aspects, and international relations. The mechanism for resolving the South Cina Sea dispute can be pursued by peaceful dispute settlement is something that must be pursued by several countries involved in the South Cina Sea conflict, choosing the peaceful settlement route to avoid conflicts with armed contact. As stipulated in Article 33 of the United Nations Charter and also does not sacrifice human lives that will be sacrificed if a decision is made to resolve disputes by violence. The Charter of the United Nations requires member states to engage in a dispute that, if continued, could endanger international peace and security.